Chemical strengthening glass manufacturing method
Patent Information
- Application Number
- JP2025064537
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-22
AI Technical Summary
【0011】 本発明に係る製造方法によれば、化学強化処理による高強度に加え、良好な防眩性も備えた化学強化ガラスを得られる。そのため、得られた化学強化ガラスは、ディスプレイ用途、特にヘッドインパクト時にも割れない強度が求められる車載ディスプレイ用途のカバーガラスに非常に好適である。
Smart Images

Figure 2026170757000001
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing chemically strengthened glass.
Background Art
[0002] In flat panel display devices such as digital cameras, mobile phones, or personal digital assistants (PDAs), a thin plate-like cover glass is arranged on the front surface of the display so as to form a region wider than the image display portion, in order to protect the display and enhance its aesthetic appearance. Although glass has a high theoretical strength, its strength is significantly reduced when it is scratched. Therefore, for cover glass that requires high strength, chemically strengthened glass having a compressive stress layer formed on the glass surface by ion exchange or the like is used.
[0003] As chemically strengthened glass, for example, Patent Document 1 discloses that by further subjecting ion-exchanged glass to acid treatment and alkali treatment, a decrease in the strength of the treated glass can be suppressed. In addition, Patent Document 2 discloses that the surface strength of glass can be further improved by controlling the amount of water vapor during ion exchange.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
Summary of Invention
Problem to be Solved by the Invention
[0005] When such chemically strengthened glass is used particularly as a cover glass for displays, in addition to high strength, it is required to impart antiglare properties that reduce the reflected image on the glass surface.
[0006] Therefore, the present invention aims to provide a manufacturing method for obtaining glass that achieves both anti-glare properties and high strength. [Means for solving the problem]
[0007] Chemical strengthening treatment involving ion exchange is known as a method for increasing the strength of glass. As disclosed in Patent Documents 1 and 2, the glass surface can be removed by further acid and alkali treatments after the ion exchange treatment. This also removes cracks on the glass surface, enabling the realization of high surface strength in the glass.
[0008] However, when ion exchange treatment, acid treatment, and alkali treatment are applied to glass with an uneven surface to impart anti-glare properties, the uneven surface changes significantly, greatly affecting the anti-glare performance.
[0009] In response to this, the inventors have found that the above problem can be solved by keeping the amount of glass surface removed by the above treatment within a certain range, and by keeping the average length roughness RSm of the glass surface before and after the above treatment within a certain range, thus completing the present invention.
[0010] In other words, the gist of this invention is as follows. [1] A method for manufacturing chemically strengthened glass, To prepare tempered glass having a pair of opposing main surfaces, and having an uneven surface on at least one of the main surfaces, At least the surface of the tempered glass having the aforementioned uneven shape is subjected to ion exchange treatment with a molten salt containing KNO3 and K2CO3. The ion-exchange treated surface is then treated with acid, and The process includes, in order, treating the acid-treated surface with alkali, The absolute value |ΔRSm| of the change in the average length roughness RSm of the surface having the uneven shape between the glass before the ion exchange treatment and the glass after the alkali treatment is 2.0 nm or less. The thickness of the surface having the aforementioned uneven shape, after removal by the ion exchange treatment, the acid treatment, and the alkali treatment, is 180 to 1000 nm. A method for manufacturing chemically strengthened glass, wherein the haze of the chemically strengthened glass is 10% or less. [2] The method for producing chemically strengthened glass according to [1], wherein the average length roughness RSm of the glass before ion exchange treatment is 10 to 50 nm. [3] A method for manufacturing chemically strengthened glass according to [1] or [2], wherein the strengthening glass is prepared by etching at least one surface of a pair of opposing main surfaces of a glass having a pair of main surfaces. [4] A method for manufacturing chemically strengthened glass according to any one of [1] to [3], wherein the ion exchange treatment is carried out in an atmosphere with a dew point temperature of 10 to 70°C. [5] A method for producing chemically strengthened glass according to any one of [1] to [4], wherein the absolute value |ΔRSm| of the change in the average length roughness RSm of the surface having the uneven shape between the glass before ion exchange treatment and the glass after alkali treatment is 1.0 nm or less. [6] A method for manufacturing chemically strengthened glass according to any one of [1] to [5], wherein the total thickness of the surface having the uneven shape removed by the ion exchange treatment, the acid treatment, and the alkali treatment is 400 to 900 nm. [7] The method for producing chemically strengthened glass according to any one of [1] to [6] above, wherein the strengthening glass contains Na as a constituent element. [8] The method for manufacturing chemically strengthened glass according to [7], wherein the strengthening glass further comprises Si and Al as constituent elements. [9] The tempered glass contains, in molar percentage terms based on oxides, SiO2: 50-80%, Al2O3: 0.1-25% Li2O: 0-10%, Na2O: 0-25% K2O: 0-11% MgO: 0-15% CaO: 0-6%, The method for producing chemically strengthened glass according to the above [8], which satisfies ZrO2: 0 to 5%.
[10] The method for producing chemically strengthened glass according to any one of the above [1] to [9], further comprising forming an antireflective film on the alkali-treated surface.
[11] The method for producing chemically strengthened glass according to the above
[10] , further comprising forming an antifouling layer on the antireflective film.
[12] The method for producing chemically strengthened glass according to any one of the above [1] to
[11] , wherein the chemically strengthened glass is used as cover glass for displays.
[13] The method for producing chemically strengthened glass according to any one of the above [1] to
[11] , wherein the chemically strengthened glass is used as cover glass for in-vehicle displays.
[14] The method for producing chemically strengthened glass according to any one of the above [1] to
[11] , wherein the chemically strengthened glass is used as cover glass for solar cell modules.
[15] The method for producing chemically strengthened glass according to any one of the above [1] to
[14] , which contributes to SDGs from at least one of the viewpoints of reducing the deterioration rate of the molten salt and reducing the output of glass waste by increasing the strength of the glass.
Effects of the Invention
[0011] According to the production method of the present invention, it is possible to obtain chemically strengthened glass that has high strength from chemical strengthening treatment and also has good antiglare properties. Therefore, the obtained chemically strengthened glass is very suitably used as cover glass for display applications, particularly in-vehicle display applications that require strength to avoid breakage even during head impact.
Modes for Carrying Out the Invention
[0012] Hereinafter, the present invention is described in detail, but the present invention is not limited to the following embodiments, and can be arbitrarily modified and implemented without departing from the gist of the present invention. In this specification, "~" indicating a numerical range is used to mean that the numerical values stated before and after it are included as the lower limit value and the upper limit value.
[0013] Method for producing chemically strengthened glass The method for producing chemically strengthened glass according to the present embodiment includes the following steps in sequence. Step 1: A step of preparing a glass for strengthening that has a pair of opposing main surfaces and has an uneven shape on at least one of the main surfaces. Step 2: A step of subjecting at least the surface having the uneven shape of the glass for strengthening prepared in Step 1 to an ion exchange treatment with a molten salt containing KNO₃ and K₂CO₃. Step 3: A step of subjecting the surface that has undergone the ion exchange treatment in Step 2 to an acid treatment. Step 4: A step of subjecting the surface that has undergone the acid treatment in Step 3 to an alkali treatment.
[0014] In the production method according to the present embodiment, the thickness removed from the surface having the uneven shape by the ion exchange treatment, acid treatment, and alkali treatment in Steps 2 to 4 is set within the range of 180 to 1000 nm, and the absolute value of the change amount |ΔRSm| of the average length roughness RSm (hereinafter sometimes simply referred to as "RSm") of the surface having the uneven shape between the glass before the ion exchange treatment in Step 2 and the alkali-treated glass obtained through Steps 2 to 4 is set to 2.0 nm or less. As a result, in addition to high surface compressive stress value and surface strength by the chemical strengthening treatment, the surface uneven shape suitable for obtaining good antiglare properties is also maintained, and a chemically strengthened glass that achieves both high strength and good antiglare properties is obtained.
[0015] Further, the chemically strengthened glass obtained by the production method according to the present embodiment has a Haze of 10% or less. Thereby, better antiglare properties in which reflection of light on the glass surface is suppressed can be obtained.
[0016] To describe the properties of a surface with an uneven shape, there are parameters related to surface roughness, as well as functional parameters such as the level difference of the core and the height of the protruding peaks (or valleys). In this embodiment, we found that by keeping the change in the average length roughness RSm in the lateral direction, which is one of the surface roughness parameters, within a certain range between before ion exchange treatment and after alkali treatment (|ΔRSm|), the anti-glare properties of the tempered glass can be maintained without significantly reducing them. The uneven shape can be expressed by Ra, RSm, etc., and in a simple way, the change in the uneven shape and optical properties can be confirmed by |ΔRSm|. In this specification, RSm is a surface texture parameter based on the content described in JIS B 0601:2013 and is a value measured in accordance with JIS B 0633:2001.
[0017] According to the method for manufacturing chemically strengthened glass of this embodiment, by performing chemical strengthening treatments such as ion exchange treatment, acid treatment, and alkali treatment on tempering glass having an uneven surface, it is possible to obtain chemically strengthened glass that is stronger than chemically strengthened glass that has only undergone ion exchange treatment, while maintaining the anti-glare properties of the glass before chemical strengthening treatment.
[0018] Furthermore, methods for separately forming chemically strengthened glass with an anti-glare layer include chemically strengthening glass that has been directly processed with a textured surface, and applying another anti-glare layer after the chemical strengthening treatment. In the former case, chemical strengthening after texture processing results in insufficient glass strength. In the latter case, applying another layer as an anti-glare layer results in insufficient glass strength, adds an extra step, and tends to be inferior in terms of heat resistance, etc., compared to direct processing of the glass.
[0019] In contrast, the manufacturing method according to this embodiment is highly versatile, applicable regardless of the shape or size of the glass, and efficient in that it can process both sides of the glass simultaneously.
[0020] The following describes each step in order.
[0021] <Step 1: Preparation of tempered glass> Step 1 in this embodiment is the step of preparing tempered glass having a pair of opposing main surfaces, with at least one of the main surfaces having an uneven shape. The tempered glass described above may be commercially available as is, or it may be obtained by adding an uneven surface to the glass.
[0022] In this embodiment, the tempered glass only needs to have an uneven surface on at least one of the pair of opposing main surfaces, and depending on the application, it can be decided whether the uneven surface is present on only one main surface or on both main surfaces. When both main surfaces have an uneven surface, the uneven surfaces of both main surfaces may be the same or different.
[0023] In this embodiment, the surface irregularities of the tempered glass preferably have an average length roughness RSm of 10 to 50 nm. From the viewpoint of affecting haze, the RSm is preferably 10 nm or more, more preferably 20 nm or more, even more preferably 30 nm or more, and even more preferably 40 nm or more. Furthermore, from the viewpoint of suppressing glare, the RSm is preferably 50 nm or less, more preferably 40 nm or less, and even more preferably 30 nm or less. The glare mentioned above refers to the degree to which unevenness in bright spots is observed, which occurs when light (image) from a displayed image is scattered by the surface of the glass plate as it passes through the plate, and the scattered light interferes with each other. This value correlates with the observer's visual judgment of glare and has been confirmed to exhibit behavior similar to human perception. The glare mentioned above is sometimes called Sparkle, and can be measured by the method described in Japanese Patent Publication No. 7119417.
[0024] In this embodiment, anti-glare properties can be imparted to the glass surface by either chemical or physical treatment, thereby creating an uneven surface. Examples of chemical treatments include etching. Physical treatments include, for example, sandblasting, which involves blasting the glass surface with crystalline silicon dioxide powder, silicon carbide powder, etc., using pressurized air, and polishing with a brush coated with crystalline silicon dioxide powder, silicon carbide powder, etc., and moistened with water.
[0025] In particular, from the viewpoint of optical properties, it is preferable to obtain the tempered glass in this embodiment by etching at least one surface of a pair of opposing main surfaces of a glass having a pair of main surfaces.
[0026] In this embodiment, the tempered glass can be of various compositions, as long as it has a composition that allows for molding and chemical strengthening. Specifically, examples include aluminosilicate glass, soda-lime glass, borosilicate glass, lead glass, alkali barium glass, and aluminoborosilicate glass.
[0027] The tempered glass in this embodiment preferably contains sodium (Na) as a constituent element, more preferably contains at least one of Si and Al, and even more preferably contains both Si and Al.
[0028] In this embodiment, a suitable composition for the tempered glass is, for example, one in which the content in molar percentage based on oxides satisfies the following conditions. SiO2: 50-80%, Al2O3: 0.1-25% Li2O: 0-10%, Na2O: 0-25% K2O: 0-11% MgO: 0-15% CaO: 0-6%, ZrO2: 0-5%.
[0029] The more specific composition of the tempered glass in this embodiment is not particularly limited, but examples include the following compositions. (i) Glass that satisfies the following content in mole percent based on oxides: SiO2: 50-80%, Al2O3: 2-25%, Li2O: 0-10%, Na2O: 0-18%, K2O: 0-10%, MgO: 0-15%, CaO: 0-5%, and ZrO2: 0-5%. (ii) Glass that satisfies the following requirements in molar percentage based on oxides: SiO2: 50-74%, Al2O3: 1-10%, Na2O: 6-14%, K2O: 3-11%, MgO: 2-15%, CaO: 0-6%, and ZrO2: 0-5%, and further satisfies the following requirements: the total content of SiO2 and Al2O3 is 75% or less, the total content of Na2O and K2O is 12-25%, and the total content of MgO and CaO is 7-15%. (iii) Glass that satisfies the following content in mole percent based on oxides: SiO2: 68-80%, Al2O3: 4-10%, Na2O: 5-15%, K2O: 0-1%, MgO: 4-15%, and ZrO2: 0-1%. (iv) Glass that satisfies the following content requirements in molar percentage based on oxides: SiO2: 67-75%, Al2O3: 0-4%, Na2O: 7-15%, K2O: 1-9%, CaO: 0% or more and less than 1%, MgO: 6-14%, and ZrO2: 0-1.5%, and further satisfies the following requirements: the total content of SiO2 and Al2O3 is 71-75%, and the total content of Na2O and K2O is 12-20%. (v) Glass that satisfies the following mass percentage content based on oxides: SiO2: 65-75%, Al2O3: 0.1-5%, MgO: 1-6%, and CaO: 1-15%, and further satisfies the total content of Na2O and K2O: 10-18%. (vi) Glass that satisfies the following mass percentage content based on oxides: SiO2: 60-72%, Al2O3: 1-10%, MgO: 5-12%, CaO: 0.1-5%, Na2O: 13-19%, and K2O: 0-5%, and further satisfies RO / (RO+R2O): 0.20-0.42 (where RO represents the total content of alkaline earth metal oxides, and R2O represents the total content of alkali metal oxides). (vii) Glass that satisfies the following requirements in molar percentages based on oxides: SiO2: 55.5-80%, Al2O3: 12-20%, Na2O: 8-25%, P2O5: 2.5% or more, and total alkaline earth metal content (MgO + CaO + SrO + BaO): 1% or more. (viii) Glass that satisfies the following requirements in molar percentage based on oxides: SiO2: 57-76.5%, Al2O3: 12-18%, Na2O: 8-25%, P2O5: 2.5-10%, and total alkaline earth metal content (MgO + CaO + SrO + BaO): 1% or more. (ix) Glass that satisfies the following content in mole percent based on oxides: SiO2: 56-72%, Al2O3: 8-20%, B2O3: 3-20%, Na2O: 8-25%, K2O: 0-5%, MgO: 0-15%, CaO: 0-15%, SrO2: 0-15%, BaO: 0-15%, and ZrO2: 0-8%.
[0030] Furthermore, the composition of the tempering glass in this embodiment is the same as the base composition of the chemically strengthened glass obtained by the manufacturing method according to this embodiment.
[0031] The manufacturing method for obtaining the tempered glass bulk in this embodiment, that is, the glass before the surface is given an uneven shape, is not particularly limited and can be manufactured by conventionally known methods. For example, by introducing the desired glass raw material into a continuous melting furnace, heating and melting the glass raw material at preferably 1500 to 1600°C, clarifying it, and then supplying it to a molding device to form the molten glass into a plate shape, and then slowly cooling it, a glass having a pair of opposing main surfaces can be produced.
[0032] Various methods can be used to form glass, such as the down-draw method, float method, roll-out method, and press method. Examples of the down-draw method include the overflow down-draw method, slot-down method, and redraw method.
[0033] The thickness of the tempered glass in this embodiment is not particularly limited, but for example, it may be 0.7 to 2.0 mm. Here, from the viewpoint of improving the handling convenience of the final product and reducing costs, the above thickness may be 0.7 mm or more, 2.0 mm or less, 1.5 mm or less, or 1.0 mm or less. Furthermore, when considering applications other than cover glass for automotive interiors, the above thickness may be 2.0 mm or more.
[0034] The shape of the tempered glass in this embodiment is not particularly limited. For example, various shapes of glass can be used, such as a flat plate with a uniform thickness, a shape with a curved surface on at least one of its front and back surfaces, or a three-dimensional shape with a bent portion.
[0035] <Step 2: Ion exchange treatment process> Step 2 in this embodiment is a step of ion-exchange treatment of at least the surface having the above-described uneven shape of the tempering glass prepared in Step 1 with a molten salt containing KNO3 and K2CO3.
[0036] By performing step 2 in this embodiment, an ion-exchanged compressive stress layer can be formed on the surface of the tempered glass. Specifically, the surface of the tempered glass is ion-exchanged to form a surface layer in which compressive stress remains.
[0037] The surface roughness of the glass before the ion exchange treatment in step 2 is preferably such that the average length roughness RSm is 10 to 50 nm. Here, from the viewpoint of the effect on haze, the RSm is preferably 10 nm or more, more preferably 20 nm or more, even more preferably 30 nm or more, and even more preferably 40 nm or more. Furthermore, from the viewpoint of suppressing glare, the RSm is preferably 50 nm or less, more preferably 40 nm or less, and even more preferably 30 nm or less.
[0038] Specifically, at temperatures below the glass transition temperature, alkali metal ions with small ionic radii on the glass surface are replaced with alkali ions with larger ionic radii by ion exchange. For example, sodium ions on the surface of tempered glass are replaced with potassium ions. This leaves compressive stress on the surface of the tempered glass, improving its strength.
[0039] In step 2 of this embodiment, the ion exchange treatment is carried out by contacting the glass with a molten salt containing potassium nitrate (KNO3), preferably a molten salt containing potassium nitrate (KNO3) and potassium carbonate (K2CO3). This causes ion exchange between Na ions on the glass surface and K ions in the molten salt, forming a high-density compressive stress layer. Furthermore, the inclusion of K2CO3 in the molten salt in addition to KNO3 is preferable from the viewpoint of forming a low-density layer in the glass during the subsequent acid treatment.
[0040] The above molten salt may contain other components in addition to KNO3 and K2CO3. Examples of other components include NaNO3, Na2CO3, and KHCO3. 3、 NaHCO 3、 Examples include Li2CO3, Rb2CO3, Cs2CO3, MgCO3, CaCO3, and BaCO3. In particular, from the viewpoint of obtaining a higher surface stress value, it is preferable that the molten salt contains NaNO3 in addition to KNO3 and K2CO3. Furthermore, the molten salt in this embodiment may contain other components besides those exemplified above.
[0041] Methods for bringing glass into contact with molten salt include applying a paste-like molten salt, spraying molten salt onto the glass, and immersing the glass in molten salt. Of these, immersion in molten salt is preferable.
[0042] The molten salt is preferably one whose melting point is below the strain point of the glass being treated with ion exchange (usually 500-600°C). For example, KNO3 has a melting point of 330°C, and NaNO3 has a melting point of 308°C. The melting point of elemental K2CO3 is 891°C, but when mixed with KNO3 or NaNO3, the eutectic point can be below 600°C.
[0043] The KNO3 content in the molten salt is preferably 50 to 100% by mass. From the viewpoint of creating a high compressive stress on the surface, the above content is preferably 50% by mass or more, more preferably 80% by mass or more, and even more preferably 95% by mass or more. In addition, the KNO3 content may be 100% by mass, i.e., the molten salt may consist only of KNO3, but from the viewpoint of salt life, the above content is preferably 95% by mass or less, may be 80% by mass or less, or 50% by mass or less.
[0044] When the molten salt contains K2CO3, the K2CO3 content in the molten salt is preferably 2 to 8% by mass. Here, from the viewpoint of creating a low-density layer, the above content is preferably 2% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and even more preferably 7% by mass or more. Also, from the viewpoint of minimizing the occurrence of undissolved material, the above content is preferably 8% by mass or less, may be 7% by mass or less, may be 5% by mass or less, or may be 3% by mass or less.
[0045] When the molten salt contains NaNO3, the NaNO3 content in the molten salt is preferably greater than 0% by mass and 10% by mass or less. Here, from the viewpoint of the ease of melting K2CO3, the above content is preferably greater than 0% by mass, may be 0.6% by mass or more, may be 3% by mass or more, and may be 5% by mass or more. Furthermore, from the viewpoint of the compressive stress of the surface layer, the above content is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 1% by mass or less, and the lower the value, the better.
[0046] The ion exchange in step 2 of this embodiment can be carried out specifically, for example, by the following procedure.
[0047] First, the tempering glass is preheated, and the molten salt is adjusted to the temperature required for ion exchange treatment. Next, the preheated glass is immersed in the molten salt in the molten salt bath for a predetermined time, after which the glass is removed from the molten salt and allowed to cool. Note that, if necessary, the tempering glass may be subjected to shaping, such as cutting, beveling, and drilling, before the ion exchange treatment.
[0048] The preheating temperature of the tempered glass in this embodiment depends on the temperature at which it is immersed in the molten salt, but can be, for example, 100°C or higher.
[0049] The temperature of the molten salt during ion exchange treatment is preferably below the strain point of the tempered glass (for example, usually 500-600°C), and more preferably between 350°C and the strain point. Here, from the viewpoint of obtaining a greater compressive stress layer depth, the temperature is preferably 350°C or higher, and more preferably 400°C or higher, and even more preferably 430°C or higher, from the viewpoint of shortening the treatment time and promoting the formation of the low-density layer described later.
[0050] In this embodiment, the immersion time of the tempering glass in the molten salt is preferably 1 minute to 10 hours. Here, from the viewpoint of balancing strength and the depth of the compressive stress layer, the above time is preferably 1 minute or more, more preferably 5 minutes or more, even more preferably 10 minutes or more, and preferably 10 hours or less, more preferably 8 hours or less, and even more preferably 4 hours or less.
[0051] In step 2 of this embodiment, it is preferable to perform the ion exchange treatment in an atmosphere in which the amount of water vapor, i.e., the dew point temperature, is controlled. When the ion exchange treatment is performed by immersing the reinforcing glass in a molten salt, the dew point temperature of the atmosphere above the molten salt is set to a specific range.
[0052] The above dew point temperature is preferably 10 to 70°C. Here, from the viewpoint of increasing the thickness of the low-density layer by step 3 described later and increasing the thickness removed in step 4, the above dew point temperature is preferably 10°C or higher, may be 25°C or higher, or may be 50°C or higher. Furthermore, from the viewpoint of suppressing a decrease in anti-glare properties due to an excessive increase in |ΔRSm|, which is the absolute value of the change in RSm between the glass before ion exchange treatment and the glass after alkali treatment, the above dew point temperature is preferably 70°C or lower, more preferably 50°C or lower, and even more preferably 25°C or lower.
[0053] As described above, by increasing the dew point temperature, that is, by increasing the amount of water vapor in the molten salt, the low-density layer formed in step 3 described later can be made thicker. Then, in step 4 described later, the low-density layer can be removed. Here, the closer the thickness of the low-density layer is to the average depth of cracks and latent defects present on the surface of the tempered glass, the greater the amount of cracks and latent defects that can be removed along with the removal of the low-density layer, thereby achieving superior surface strength in the chemically strengthened glass.
[0054] The thickness of the low-density layer described above is, for example, about 100-200 nm when ion exchange treatment is performed without introducing water vapor, i.e., without controlling the dew point temperature. However, by performing ion exchange treatment in an atmosphere with a dew point temperature of 10°C or higher, the thickness can be increased to, for example, 300 nm or more. Note that the specific numerical value of the thickness described above will vary depending on the glass composition and conditions such as the type, temperature, and time of the molten salt used for ion exchange.
[0055] The dew point temperature in step 2 can be controlled by introducing water vapor into the atmosphere near the interface of the molten salt and / or before and / or simultaneously with step 2. The above-mentioned introduction of water vapor may involve introducing water vapor itself, introducing a gas containing water vapor, directly bubbling water (liquid), or introducing water vapor or a gas containing water vapor into the space above the molten salt. Furthermore, water (liquid) itself may be introduced by dripping it onto the molten salt, provided that a steam explosion does not occur.
[0056] In this embodiment, the RSm of the glass surface hardly changes before and after step 2. Therefore, the RSm of the glass surface after step 2 and before being subjected to step 3 can be considered equivalent to the RSm value of the tempered glass prepared in step 1. Specifically, the average length roughness RSm of the surface of the tempered glass of this embodiment, which has an uneven shape, is preferably 10 to 50 nm in order to fully exhibit the anti-glare treatment effect. Here, RSm is preferably 10 nm or more, more preferably 20 nm or more, may also be 30 nm or more, may also be 40 nm or more, and may also be 50 nm or less, may also be 40 nm or less, or may be 30 nm or less.
[0057] The glass that has undergone the ion exchange treatment in step 2 of this embodiment is washed as needed before being subjected to step 3.
[0058] The above cleaning may be carried out using, for example, industrial water, deionized water, etc. The industrial water should be treated as needed. Among these, cleaning with deionized water is preferred.
[0059] The washing conditions vary depending on the washing solution used, but when using deionized water, washing at 0 to 100°C is preferable from the viewpoint of completely removing the attached salt.
[0060] The above cleaning methods include, for example, immersing ion-exchange treated glass in a tank containing ion-exchanged water, exposing the glass surface to running water, or spraying cleaning solution onto the glass surface using a shower.
[0061] <Step 3: Acid Treatment Process> Step 3 in this embodiment is a step of acid-treating the surface that has been ion-exchange-treated in step 2. Furthermore, in step 2, if there is a glass surface that has not undergone ion exchange treatment, this does not mean that such surface should not be acid-treated. It is optional whether or not to acid-treat such surface together with the ion-exchange-treated surface.
[0062] The acid treatment in step 3 of this embodiment is performed by bringing the surface of the glass to be treated into contact with an acid. Specifically, for example, this can be done by immersing the glass that has undergone ion exchange treatment in step 2 into an acidic solution.
[0063] Acid treatment replaces Na and / or K on the glass surface with H. This alters the glass surface, resulting in a lower density and the formation of a low-density layer.
[0064] The solution used for acid treatment in this embodiment only needs to be acidic, i.e., have a pH of less than 7, and may be a weak acid or a strong acid. Preferred solutions include, for example, hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, acetic acid, oxalic acid, carbonic acid, and citric acid. These acids may be used individually or in combination.
[0065] The temperature for acid-alkali treatment varies depending on the type, concentration, and duration of the acid used. For example, when performing acid treatment with a 6.0% by mass HNO3 solution for 120 seconds, followed by alkali treatment with a 4.0% by mass NaOH solution for 120 seconds, there is no strict specification for the temperature of the acid-alkali treatment, but it is preferably 100°C or lower, and preferably 20-60°C. From the viewpoint of removing the low-density layer, the above temperature is preferably 20°C or higher, may be 60°C or higher, or 80°C or higher. From the viewpoint of safety, the above temperature is preferably 100°C or lower, more preferably 80°C or lower, and even more preferably 60°C or lower.
[0066] The time required for the acid treatment varies depending on the type and concentration of the acid used and the temperature, but is preferably 10 seconds to 5 hours. From the viewpoint of making the low-density layer thicker than a certain amount, the above time is preferably 10 seconds or more, more preferably 30 seconds or more, and even more preferably 60 seconds or more. Furthermore, from the viewpoint of productivity and minimizing the change in RSm of the chemically strengthened glass compared to the tempered glass, the above time is preferably 5 hours or less, more preferably 2 hours or less, even more preferably 1 hour or less, even more preferably 30 minutes or less, and particularly preferably 180 seconds or less.
[0067] The concentration of the solution used for acid treatment varies depending on the type of acid used, the time, and the temperature, but is preferably, for example, 0.1% to 20% by mass. Here, from the viewpoint of efficiently forming a low-density layer, the above concentration is preferably 0.1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more. Furthermore, from the viewpoint of preventing container corrosion, the above concentration is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less.
[0068] In this embodiment, the low-density layer formed by the acid treatment in step 3 is removed by the alkali treatment in step 4, which will be described later. Therefore, the thicker the low-density layer, the easier it is to remove the glass surface. The thickness of the low-density layer can be controlled by the molten salt, temperature, and time used in the ion exchange treatment in step 2.
[0069] From the viewpoint of glass surface removalability, the density of the low-density layer is preferably lower than the density of the region (bulk) deeper than the ion-exchange treated compressive stress layer.
[0070] The thickness of the low-density layer can be determined from the period (Δθ) measured by X-ray reflectometry (XRR). The density of the low-density layer is determined by the critical angle (θc) measured by XRR. Alternatively, a simpler method may be used to observe the cross-section of the glass using a scanning electron microscope (SEM) to confirm the formation and thickness of the low-density layer.
[0071] In this embodiment, the average length roughness RSm of the surface of the glass having an uneven shape after the acid treatment in step 3 is preferably 10 to 50 nm. Here, the RSm is preferably 10 nm or more, more preferably 20 nm or more, may be 30 nm or more, may be 40 nm or more, and may be 50 nm or less, may be 40 nm or less, or may be 30 nm or less.
[0072] Furthermore, the absolute value of the change in RSm of the glass surface with an uneven shape before and after the acid treatment in step 3, |ΔRSm|, is preferably 1.0 nm or less, more preferably 0.7 nm or less, and even more preferably 0.4 nm or less, from the viewpoint of changes in optical properties. The lower limit of |ΔRSm| is not particularly limited, but may be, for example, 0.1 nm or more.
[0073] <Step 4: Alkali treatment process> Step 4 in this embodiment is a step of alkali treatment on the surface that was acid-treated in step 3. In addition, if there is a glass surface that has not been acid-treated in step 3, this does not mean that the surface will not be alkali-treated. The surface may be alkali-treated together with the acid-treated surface, or it may not be alkali-treated; it is entirely at the discretion of the user.
[0074] Alkali treatment is performed by bringing the surface treated with acid in step 3 into contact with a basic solution. For example, alkali treatment is performed by immersing the glass obtained in step 3 in a basic solution. This alkaline treatment can remove part or all of the low-density layer formed by the acid treatment in step 3.
[0075] The solution used for alkaline treatment is not particularly limited as long as it is basic, and its pH must be greater than 7. The basic solution may be a weak base or a strong base. As the above solution, bases such as sodium hydroxide, potassium hydroxide, potassium carbonate, and sodium carbonate are preferred. These bases may be used individually or in combination.
[0076] The temperature for alkaline treatment varies depending on the type and concentration of the base used and the duration, but is preferably between 0 and 100°C. Here, from the viewpoint of completely removing the low-density layer, the temperature is preferably 0°C or higher, more preferably 10°C or higher, and even more preferably 20°C or higher. Furthermore, from the viewpoint of preventing glass corrosion, the temperature is preferably 100°C or lower, more preferably 80°C or lower, and even more preferably 60°C or lower.
[0077] The time required for alkaline treatment varies depending on the type and concentration of the base used and the temperature, but is preferably 10 seconds to 5 hours. Here, from the viewpoint of removing the low-density layer without deficiency, the above time is preferably 10 seconds or more, and more preferably 1 minute or more. Also, from the viewpoint of productivity, the above time is preferably 5 hours or less, more preferably 2 hours or less, even more preferably 1 hour or less, even more preferably 30 minutes or less, and particularly preferably 180 seconds or less.
[0078] The concentration of the solution used for alkaline treatment varies depending on the type of base used, the time, and the temperature, but is preferably, for example, 0.1 to 20% by mass. Here, from the viewpoint of glass surface removal, the above concentration is preferably 0.1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and also preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less.
[0079] The alkali treatment described above removes some or all of the low-density layer into which hydrogen (H) penetrated during the acid treatment in step 3, thereby obtaining chemically strengthened glass with improved surface strength. Furthermore, since scratches present on the glass surface are also removed by the removal of the low-density layer, this is also considered to contribute to the improvement in strength. Furthermore, it is preferable to follow the alkaline treatment with a further step of cleaning the glass using the same method as described above.
[0080] In the manufacturing method according to this embodiment, the total thickness removed by the processing in steps 2 to 4 from the surface of the tempered glass having an uneven shape obtained in step 1 is preferably 180 to 1000 nm, and more preferably 400 to 900 nm. Here, the total thickness is preferably 180 nm or more, more preferably 200 nm or more, even more preferably 300 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving surface strength. Furthermore, from the viewpoint of making the absolute value |ΔRSm| of the difference in RSm of the surface having an uneven shape in the glass before ion exchange treatment and the glass after alkali treatment within a suitable range, and from the viewpoint of improving surface strength, the total thickness is preferably 1000 nm or less, more preferably 950 nm or less, even more preferably 900 nm or less, and even more preferably 850 nm or less. Note that the above total thickness is the sum of the thicknesses on one surface. If the surfaces of both main surfaces of the tempered glass have an uneven shape and each surface is removed by the processing in steps 2 to 4, it is preferable that the sum of the thicknesses within the above range is removed from each surface.
[0081] The total thickness mentioned above can be calculated by using the weight of the tempering glass obtained in step 1 and the weight of the chemically strengthened glass obtained through steps 1 and 4, and converting them to thickness using the following formula. Removal amount (thickness, nm) = {[Weight of tempered glass obtained in step 1 (g) - Weight of chemically strengthened glass obtained in step 4 (g)] / Specific gravity of glass (g / cm³) 3 ) / Area of the glass surface (cm²) 2 ) / 2}×10 -7
[0082] <Optional steps> The method for manufacturing chemically strengthened glass according to this embodiment may further include a step of forming an anti-reflective film on the surface of the glass having an uneven shape after step 4. Furthermore, the method for manufacturing chemically strengthened glass according to this embodiment may include a step of forming an antifouling layer on the surface of the glass having an uneven shape after step 4, or it may include a step of forming an antifouling layer on the anti-reflective film.
[0083] By applying an anti-reflective (AR) coating, reflectivity is reduced, lessening glare caused by reflected light. Furthermore, when chemically strengthened glass is used in visible applications such as display cover glass, visibility is also improved.
[0084] The formation of the above anti-reflective film can be carried out using conventionally known methods and is not particularly limited as long as it suppresses light reflection. For example, high refractive index layers and low refractive index layers may be alternately laminated.
[0085] By incorporating an anti-finger-print (AFP) layer, the adhesion of various types of dirt such as fingerprints, sweat, and dust is suppressed, making dirt less noticeable.
[0086] The antifouling layer is preferably provided on a surface having an uneven shape, and may be further provided on top of an anti-reflective film.
[0087] The method for forming the antifouling layer can be any conventionally known method, and is not particularly limited as long as it provides antifouling properties. For example, it may be formed by applying a composition containing a compound selected from the group consisting of antifouling, water repellency, and oil repellency.
[0088] Examples of the above-mentioned compounds include fluorine-containing compounds. As the fluorine-containing compound mentioned above, fluorine-containing organic compounds, that is, compounds having a fluorine-containing organic group, are preferred. Examples of fluorine-containing organic compounds include fluorine-containing organosilicon compounds.
[0089] In the manufacturing method according to this embodiment, when forming an anti-reflective film on the surface of the chemically strengthened glass having an uneven shape, other arbitrary layers may be formed between them, such as an adhesion layer.
[0090] The adhesion layer is not particularly limited, but may be, for example, a metal oxide layer or a metal nitride layer containing one or more selected from the group consisting of ZrOx, TiOx, SiNx, ZnOx, TaOx, NbOx, SnOx, and AlOx.
[0091] The manufacturing method according to this embodiment is also suitable because it can contribute to the SDGs from the viewpoint of reducing the degradation rate of molten salt and reducing the amount of glass waste produced by increasing the strength of the glass.
[0092] Chemically strengthened glass In the chemical strengthening process, ion exchange occurs only on the glass surface, and the composition of the center of the thickness of the chemically strengthened glass obtained after alkali treatment is almost identical to the base composition. The chemically strengthened glass obtained by the method described above in "Method for Manufacturing Chemically Strengthened Glass" shows little change in the average length roughness RSm of the surface having an uneven shape due to the ion exchange treatment, acid treatment, and alkali treatment, i.e., chemical strengthening treatment, which are steps 2 to 4. Specifically, the absolute value of the change in RSm of the surface having an uneven shape of the glass before the ion exchange treatment in step 2 and the RSm of the surface having an uneven shape of the glass after the alkali treatment in step 4, |ΔRSm|, is preferably 2.0 nm or less, more preferably 1.0 nm or less, and even more preferably 0.5 nm or less. Furthermore, the lower limit of |ΔRSm| is not particularly limited, but for example, it is 0.1 nm or more. The above |ΔRSm| can be adjusted by the thickness of the low-density layer formed by alteration in the acid treatment of step 2, and the amount of surface material removed in the alkali treatment of step 3.
[0093] In this embodiment, the RSm value of the surface of the chemically strengthened glass having an uneven shape may be greater or less than the RSm of the surface of the glass having an uneven shape before ion exchange treatment, as long as the absolute value |ΔRSm| is 2.0 nm or less.
[0094] In this embodiment, the RSm value of the surface of the chemically strengthened glass having an uneven shape is preferably, for example, 10 to 50 nm. Here, from the viewpoint of the effect on haze, the RSm is preferably 10 nm or more, more preferably 20 nm or more, even more preferably 30 nm or more, and even more preferably 40 nm or more. Furthermore, from the viewpoint of suppressing glare, the RSm is preferably 50 nm or less, more preferably 40 nm or less, and even more preferably 30 nm or less.
[0095] In this embodiment, the chemically strengthened glass preferably has a haze of 10% or less. From the viewpoint of achieving better anti-glare properties and good visibility, such as when used as a cover glass for a display, the haze is more preferably 5% or less, and even more preferably 1% or less. The lower limit of the haze is not particularly limited, but for example, it is 0.1% or more. Haze as used herein is measured according to JIS K 7136:2000 (ISO 14782:1999).
[0096] One indicator used to evaluate the anti-glare properties of glass is emissivity, also known as Diffusion. Emissivity represents the degree to which the reflected image of an object (e.g., a light source) placed around the glass plate matches the original object, and it has been confirmed to show a good correlation with the observer's visual assessment of anti-glare properties. Specifically, Diffusion can be measured by the method described in Japanese Patent Publication No. 7119417.
[0097] In this embodiment, the diffusion of chemically strengthened glass varies depending on the glass composition. Therefore, instead of using the diffusion value of the chemically strengthened glass itself, the diffusion of glass of the same composition with no surface irregularities is used as a reference, and the diffusion is evaluated based on the percentage change from that value.
[0098] If the above percentage change is 10% or less, the effect of the processing in steps 1 to 4 on anti-glare properties is small and good, which is preferable, and if the above percentage change is 5% or less, it is even more preferable.
[0099] In this embodiment, the transmittance of the chemically strengthened glass is preferably 80% or higher, and the higher the transmittance, the better. Here, the above transmittance refers to the visible light transmittance, which means that the glass transmits an average of 80% or more of light in the wavelength range of 400 to 1100 nm (the average transmittance is 80% or higher). The average transmittance of light in the wavelength range of 400 to 1100 nm is a value measured using an integrating sphere and is a value calculated for a thickness of 1.3 mm. Alternatively, for simplicity, the transmittance at any number of points in the above wavelength range of 400 to 1100 nm may be measured, and the average value of these values may be used as the transmittance.
[0100] In this embodiment, the strength of the chemically strengthened glass can be indicated by the surface compressive stress value (CS) and the depth of the compressive stress layer (DOL). These can be measured using, for example, an EPMA (electron probe microanalyzer) or a surface stress meter (e.g., Orihara Corporation's FSM-6000).
[0101] The above surface compressive stress value is preferably, for example, 600 to 1100 MPa. Here, the above surface compressive stress value is preferably 600 MPa or more, more preferably 800 MPa or more, and even more preferably 1000 MPa or more, with higher values indicating higher surface strength. On the other hand, from the viewpoint of salt life, the above compressive stress value may be 1000 MPa or less, or 800 MPa or less.
[0102] The compressive stress layer depth is preferably, for example, 10 to 45 μm. Here, from the viewpoint of resistance to scratches, the compressive stress layer depth is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more. Also, from the viewpoint of salt life, the compressive stress layer depth may be 30 μm or less, or 20 μm or less.
[0103] In this embodiment, surface strength is cited as an indicator of the strength of the chemically strengthened glass. In this specification, surface strength is a value obtained by a ring-on-ring test. In the ring-on-ring test described above, the chemically strengthened glass is placed horizontally on a receiving jig (a ring with a diameter of 30 mm) with the uneven surface facing downwards, and the chemically strengthened glass is pressurized using a pressure jig (a ring with a radius of 10 mm) made of SUS304 (JIS G 4304:2015, JIS G 4305:2015). The downward speed of the pressure jig during this process is set to 0.5 mm / min. The process of measuring the load (MPa) at which chemically strengthened glass breaks under pressure is repeated 10 times, and the average value of these 10 measurements is taken as the surface strength (MPa).
[0104] In this embodiment, the surface strength of the chemically strengthened glass is preferably 1100 MPa or higher, more preferably 1400 MPa or higher, and the higher the better.
[0105] The applications of the chemically strengthened glass in this embodiment are not particularly limited, but it is preferably used as cover glass for displays such as mobile phones, digital cameras, or touch panel displays, or as cover glass for solar cell modules. In particular, it is also preferable to use it as cover glass for automotive displays where higher strength and good anti-glare properties are required. [Examples]
[0106] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. Examples 1 and 6 are comparative examples, while Examples 2 to 5 and 7 are examples of actual cases.
[0107] [Example Test] <Example 1> A textured surface with anti-glare properties was formed on one main surface of a glass plate (manufactured by AGC Inc., Dragontrail®, glass material 1), thereby obtaining tempered glass (50 mm × 50 mm × 0.7 mm thick) having a textured surface. The RSm of this tempered glass, i.e., the glass before ion exchange treatment, was 20.08 nm, and the Haze was 4.66% (Step 1). The RSm of the glass plate before forming the textured surface was 107.61 nm. Next, the strengthening glass obtained above was immersed in a molten salt (KNO3:NaNO3 = 98.2:1.8 (mass ratio)) at 415°C for 5 hours to perform ion exchange treatment (step 2) and obtain chemically strengthened glass.
[0108] <Example 2> The tempered glass obtained in the same manner as in Step 1 of Example 1 above was immersed in a molten salt (KNO3:K2CO3:NaNO3 = 88.6:8.1:3.3 (mass ratio)) at 435°C for 3 hours to undergo ion exchange treatment (Step 2). Next, the glass was immersed in a 6.0% by mass nitric acid (HNO3) solution and acid-treated by agitation at 40°C for 120 seconds (step 3), and the acid-treated glass was washed with pure water. Next, the glass was immersed in a 4.0% by mass sodium hydroxide (NaOH) solution and subjected to alkaline treatment by agitation at 40°C for 120 seconds (step 4). After the alkaline treatment, the glass was washed with pure water to obtain chemically strengthened glass.
[0109] <Examples 3-6> Chemically strengthened glass was obtained in the same manner as in Example 2, except that the ion exchange treatment in step 2 of Example 2 was performed in an atmosphere controlled to the dew point temperature shown in Table 1. The dew point temperature was controlled by blowing water vapor into the molten salt.
[0110] <Example 7> A textured surface with anti-glare properties was formed on one main surface of a glass plate (manufactured by AGC Inc., Dragontrail® Pro, glass material 2), thereby obtaining tempered glass (50 mm × 50 mm × 0.7 mm thick) having a textured surface. The RSm of this tempered glass, i.e., the glass before ion exchange treatment, was 26.14 nm, and the Haze was 4.02% (Step 1). The tempered glass obtained above was immersed for 3 hours in a molten salt (KNO3:K2CO3:NaNO3 = 85.6:8.1:6.3 (mass ratio)) at 435°C with a dew point temperature controlled to 26.17°C, and underwent ion exchange treatment (Step 2). Next, the glass was immersed in a 6.0% by mass nitric acid (HNO3) solution and acid-treated by agitation at 40°C for 120 seconds (step 3), and the acid-treated glass was washed with pure water. Next, the glass was immersed in a 4.0% by mass sodium hydroxide (NaOH) solution and subjected to alkaline treatment by agitation at 40°C for 120 seconds (step 4). After the alkaline treatment, the glass was washed with pure water to obtain chemically strengthened glass.
[0111] "evaluation" <RSm> For the glass obtained in each example, the RSm of the surface with an uneven shape was measured. Specifically, for Example 1, the RSm of the glass after ion exchange treatment was measured, and for Examples 2 to 7, the RSm of the glass after alkali treatment was measured. RSm is a surface texture parameter based on the content described in JIS B 0601:2013, and was measured using a white-light interferometry laser microscope (VKX-3000, manufactured by Keyence Corporation) in accordance with JIS B 0633:2001. The results are shown in Table 1. In Table 1, the absolute value of |ΔRSm|, which is the change in the average length roughness RSm of the surface with an uneven shape, between the glass before ion exchange treatment and the glass after alkali treatment, is shown in the "|ΔRSm|" column. Note that in Example 1, since steps 3 and 4 were not followed, the "|ΔRSm|" column above shows the absolute value of the change in RSm between the glass before ion exchange treatment and the glass after ion exchange treatment, and the value is enclosed in parentheses.
[0112] <Removal amount> Using the weight of the tempered glass obtained in step 1 and the weight of the chemically strengthened glass, the thickness of the surface with an uneven shape removed by the processes in steps 2 to 4 (step 2 in Example 1) was determined using the method described above. The results are shown in Table 1.
[0113] <Haze> The haze of the tempering glass obtained in step 1 and the haze of the final chemically strengthened glass were measured using an NDH-7000 (turbidimeter, manufactured by Nippon Denshoku Industries Ltd.) in accordance with JIS K 7136:2000. The results are shown in Table 1.
[0114] <Anti-glare property: Diffusion> The diffusion of the glass before the surface irregularities were formed in Step 1, and the resulting chemically strengthened glass, was measured using an SMS-1000 (Display-Messtechnik & Systeme) in accordance with JIS R 3106:2019. The diffusion value of the glass before the surface irregularities were formed in Step 1 was used as the baseline, and the percentage change in the diffusion of the resulting chemically strengthened glass was calculated as ΔDiffusion. The results are shown in Table 1. As an evaluation criterion, a change rate of 5% or less is considered very good, a change rate between 5% and 10% is considered good, and a change rate greater than 10% is considered poor.
[0115] <Transmittance> The transmittance of the chemically strengthened glass obtained in Example 2 was measured using a spectrophotometer (SCINCO, VSM-8S-2301). Specifically, the transmittance at wavelengths of 550 nm, 880 nm, and 940 nm was measured, and the average value was taken as the transmittance. As a result, a transmittance of 91% was confirmed.
[0116] <Glass Strength> The surface compressive stress (CS) and compressive stress layer depth (DOL) of chemically strengthened glass were measured using a surface stress meter (FSM-6000, Orihara Corporation). The results are shown in Table 1.
[0117] <Glass surface strength> The surface strength of the chemically strengthened glass was determined by a ring-on-ring test. Specifically, the chemically strengthened glass was placed horizontally on a receiving jig (a ring with a diameter of 30 mm) with the uneven surface facing downwards, and the chemically strengthened glass was pressurized using a SUS304 pressurizing jig (a ring with a radius of 10 mm). The downward speed of the pressurizing jig during this process was set to 0.5 mm / min. The process of measuring the load (MPa) at which chemically strengthened glass broke under pressure was repeated 10 times, and the average value of these 10 measurements was taken as the surface strength (MPa). The results are shown in Table 1. As an evaluation criterion, a surface strength of 1400 MPa or higher is considered very good, 1100 MPa or higher but less than 1400 MPa is considered good, and less than 1100 MPa is considered poor.
[0118] [Table 1]
[0119] From the above results, it was confirmed that high surface strength can be achieved by applying acid treatment and alkali treatment in addition to ion exchange treatment to tempered glass with an uneven surface. On the other hand, it was found that if the amount of surface material removed by acid treatment and alkali treatment becomes too large, the absolute value of the change in the average length roughness RSm of the surface with an uneven shape, represented by |ΔRSm|, between the glass before ion exchange treatment and the glass after alkali treatment, i.e., the change in the surface unevenness, becomes very large, and the surface strength also decreases. If the amount of surface material removed is too large, in addition to the above, the change in anti-glare properties, represented by ΔDiffusion, also becomes large, and the good anti-glare properties that the tempered glass had cannot be maintained. [Industrial applicability]
[0120] According to the manufacturing method of the present invention, glass that achieves both anti-glare properties and high strength can be obtained. Therefore, the chemically strengthened glass in this embodiment is suitable for cover glass for displays such as mobile phones, digital cameras, or touch panel displays, and for cover glass for solar cell modules, and is even more suitable for cover glass for automotive displays where higher strength is required.
Claims
1. A method for manufacturing chemically strengthened glass, To prepare tempered glass having a pair of opposing main surfaces, and having an uneven surface on at least one of the main surfaces, At least the surface of the tempered glass having the aforementioned uneven shape is KNO 3 and K 2 CO 3 The ion exchange treatment is performed with a molten salt containing the following: The ion-exchange treated surface is then treated with acid, and The process includes, in order, treating the acid-treated surface with alkali, The absolute value |ΔRSm| of the change in the average length roughness RSm of the surface having the uneven shape between the glass before the ion exchange treatment and the glass after the alkali treatment is 2.0 nm or less. The thickness of the surface having the aforementioned uneven shape, after removal by the ion exchange treatment, the acid treatment, and the alkali treatment, is 180 to 1000 nm. A method for manufacturing chemically strengthened glass, wherein the haze of the chemically strengthened glass is 10% or less.
2. The method for producing chemically strengthened glass according to claim 1, wherein the average length roughness RSm of the glass before the ion exchange treatment is 10 to 50 nm.
3. A method for manufacturing chemically strengthened glass according to claim 1 or 2, wherein the strengthening glass is prepared by etching at least one surface of a pair of opposing main surfaces of a glass having a pair of main surfaces.
4. A method for producing chemically strengthened glass according to claim 1 or 2, wherein the ion exchange treatment is performed in an atmosphere with a dew point temperature of 10 to 70°C.
5. A method for producing chemically strengthened glass according to claim 1 or 2, wherein the absolute value of the change in the average length roughness RSm of the surface having the uneven shape between the glass before the ion exchange treatment and the glass after the alkali treatment is 1.0 nm or less, |ΔRSm|.
6. A method for producing chemically strengthened glass according to claim 1 or 2, wherein the total thickness of the surface having the uneven shape removed by the ion exchange treatment, the acid treatment, and the alkali treatment is 400 to 900 nm.
7. The method for producing chemically strengthened glass according to claim 1 or 2, wherein the strengthening glass contains Na as a constituent element.
8. The method for producing chemically strengthened glass according to claim 7, wherein the strengthening glass further comprises Si and Al as constituent elements.
9. The tempered glass has an oxide content expressed in mole percent, based on the oxide, Yes 2 :5~80%、 Al 2 O 3 : 0.1-25 Li 2 O: 0~10%、 Na 2 O:0~25%、 K 2 O: 0~111%, MgO: 0-15%, CaO: 0-6%, and ZrO 2 A method for producing chemically strengthened glass according to claim 8, satisfying the requirement of 0 to 5%.
10. A method for producing chemically strengthened glass according to claim 1 or 2, further comprising forming an anti-reflective film on the surface of the alkali-treated glass.
11. A method for producing chemically strengthened glass according to claim 10, further comprising forming an antifouling layer on the anti-reflective film.
12. The method for manufacturing chemically strengthened glass according to claim 1 or 2, wherein the chemically strengthened glass is used as a cover glass for a display.
13. The method for manufacturing chemically strengthened glass according to claim 1 or 2, wherein the chemically strengthened glass is used as a cover glass for an in-vehicle display.
14. The method for manufacturing chemically strengthened glass according to claim 1 or 2, wherein the chemically strengthened glass is used as a cover glass for a solar cell module.
15. A method for producing chemically strengthened glass according to claim 1 or 2, which contributes to the SDGs from the viewpoint of reducing the rate of deterioration of the molten salt and reducing the amount of glass waste produced by increasing the strength of the glass.
Citation Information
Patent Citations
Retrieving system of picture response information
JP1982020866A
Ceramic substrate
JP1987088392A